2015
DOI: 10.1021/acsami.5b04314
|View full text |Cite
|
Sign up to set email alerts
|

Self-Healing of Core–Shell Magnetic Polystyrene Nanocomposites

Abstract: High heat generation is reported in core-shell magnetic nanoparticle polystyrene (PS) nanocomposites (3.5, 10 wt %) when they are placed in a high-frequency ac magnetic field. These magnetic nanoparticles with cobalt iron oxide core and manganese iron oxide shell were synthesized and characterized by wide-angle X-ray scattering (WAX), thermal gravimetric analysis (TGA), transmission electron microscopy (TEM), and ac field gradient magnetometery. When placed in a high-frequency ac magnetic field, the thermal en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…[34] Since then the approach was carried over to other polymer systems, including styrene, ethylene-vinyl acetate and propylene-ethylene-1-butene. [35][36][37] Hohlbein et al have also shown that the heat generated in the alternating magnetic field accelerates supramolecular healing mechanisms, in this case purchased from Alfa Aesar. Sodium bicarbonate (> 99%) was purchased from Fluka.…”
Section: Introductionmentioning
confidence: 99%
“…[34] Since then the approach was carried over to other polymer systems, including styrene, ethylene-vinyl acetate and propylene-ethylene-1-butene. [35][36][37] Hohlbein et al have also shown that the heat generated in the alternating magnetic field accelerates supramolecular healing mechanisms, in this case purchased from Alfa Aesar. Sodium bicarbonate (> 99%) was purchased from Fluka.…”
Section: Introductionmentioning
confidence: 99%
“…Under the influence of a high magnetic field, the magnetically responsive fillers vibrate and agitate, increasing the temperature inside the polymer matrix, also referred to as Néel relaxation. [ 124 ] Depending on the nature of the polymer, this can lead to one of two responses. First, the increased temperature of the polymer can lead to surface rearrangement, surface approach, and then wetting followed by chain diffusion and randomization as time progresses during the self‐healing process.…”
Section: Self‐healing Under Extreme Environmentsmentioning
confidence: 99%
“…This initiated polymer melt flow into the microcrack, resulting in a visually observed self‐healing effect. [ 124 ]…”
Section: Self‐healing Under Extreme Environmentsmentioning
confidence: 99%
“…With these three requirements matched, the particles were observed to automatically migrate toward the surface of electrical tree channels, generating localized high temperature, and to re-disperse after remolding the damaged regions ( Figure 5). [61] Different from previous self-healing research using superparamagnetic nanoparticles in which the edges of separated parts have to be put in good contact before healing, [136][137][138] the emerging approach with defect-targeted migration of the nanoparticles can repeatedly heal hollow tree channels and restore insulating properties. Interestingly, only less than 0.1 vol% of the superparamagnetic nanoparticles was found to be sufficient for the healing, which was attributed to the automatic and targeted transport and assembly of the nanoparticles toward the defect site.…”
Section: Remolding Of Multiscale Damage Via Defect-targeted Superparamentioning
confidence: 99%